(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
An existential-phenomenological analysis of eight existential tensions situated in the university context, developed from empirical work, is presented as the ’Eight Tensions Framework’. Originally formulated for students and their tutors, therapists and coaches to use when considering personal growth at university, it can also be adapted for use with a wider client base.